Iconography of abnormal non-neuronal cells in pediatric focal cortical dysplasia type IIb and tuberous sclerosis complex - Zhang, Joyce; Argueta, Deneen; Tong, Xiaoping; Vinters, Harry V.; Mathern, Gary W.; Cepeda, Carlos (Frontiers in Cellular Neuroscience, 2025)
Once believed to be the culprits of epileptogenic activity, the functional properties of balloon/giant cells (BC/GC), commonly found in some malformations of cortical development including focal cortical dysplasia type IIb (FCDIIb) and tuberous sclerosis complex (TSC), are beginning to be unraveled. These abnormal cells emerge during early brain development as a result of a hyperactive mTOR pathway and may express both neuronal and glial markers. A paradigm shift occurred when our group demonstrated that BC/GC in pediatric cases of FCDIIb and TSC are unable to generate action potentials and lack synaptic inputs. Hence, their role in epileptogenesis remained obscure. In this review, we provide a detailed characterization of abnormal non-neuronal cells including BC/GC, intermediate cells, and dysmorphic/reactive astrocytes found in FCDIIb and TSC cases, with special emphasis on electrophysiological and morphological assessments. Regardless of pathology, the electrophysiological properties of abnormal cells appear more glial-like, while others appear more neuronal-like. Their morphology also differs in terms of somatic size, shape, and dendritic elaboration. A common feature of these types of non-neuronal cells is their inability to generate action potentials. Thus, despite their distinct properties and etiologies, they share a common functional feature. We hypothesize that, although the exact role of abnormal non-neuronal cells in FCDIIb and TSC remains mysterious, it can be suggested that cells displaying more glial-like properties function in a similar way as astrocytes do, i.e., to buffer K+ ions and neurotransmitters, while those with more neuronal properties, may represent a metabolic burden due to high energy demands but inability to receive or transmit electric signals. In addition, due to the heterogeneity of these cells, a new classification scheme based on morphological, electrophysiological, and gene/protein expression in FCDIIb and TSC cases seems warranted.